Enhanced Youden's index with net benefit: A feasible approach for optimal‐threshold determination in shared decision making. Issue 2 (18th November 2019) - Lin, Senlin; Ma, Yingyan; Zou, Haidong
Abstract: Objectives: To establish an enhanced Youden's index with net benefit, as a scientific method for optimal‐threshold determination in shared decision making. Method: We redefined the Youden's index by changing the target function from the maximization of accuracy to the maximization of net benefit and established the process for pursuing the patient's individual optimal‐threshold. In addition, we illustrated how the enhanced Youden's index works with an example of cataract operation decision making using the data from Shanghai, China. Results: We modified the method of calculating net benefit in decision curve analysis and fused it with Youden's index to expand the purpose from finding a threshold with the best test accuracy to finding one with the best net benefit. As an example, we used the enhanced Youden's index to establish an optimal‐thresholds list for cataract operation decision making. Then, we calculated three imaginary patients' respective thresholds after integrating the local recovery rate, their visual activities, and individual preferences. The results demonstrated that the thresholds of patients with the same objective examination results might vary widely due to their individual preferences. Therefore, the thresholds are more individualized according to the enhanced Youden's index. Conclusion: The enhanced Youden's index can establish the optimal‐thresholds from the perspective of maximization of patients' net benefit and provide a quantifiable method for shared decision making.